SED-brachydactyly and distinctive speech: Report of a new familial case - Oliveira, Camila Ive Ferreira [UNESP]; Filho, Guaracy Carvalho; Souza, Antonio Soares; Fett-Conte, Agnes Cristina (International Scientific Information, 2011)
Background: Spondyloepiphyseal dysplasia-brachydactyly and distinctive speech (SED-BDS) is a syndrome characterized by short stature, disproportionately short limbs, peculiar face, thick and abundant hair, high-pitched and coarse voice, small epiphyses, brachymetacarpalia, brachymetatarsalia and brachy-phalangia of fingers and toes, small pelvis and delayed carpal bone age, among other features. Case Report: We report a Brazilian patient with father, brother and sister presenting with the same typical features of the syndrome. Clinically, he showed disproportionately short stature, rhizo-meso-acromelic shortness of the extremities, short hands and feet, a peculiar distinctive high-pitched voice, peculiar facies, and other features already reported as characteristic of this syndrome. Radiographic fndings included shape anomalies of the vertebral bodies such as cuboid-shaped vertebral bodies, mild scoliosis, short and broad tubular bones, brachymetacarpalia, brachymetatarsalia, and brachy-dactyly, lumbar hyperlordosis, generalized osteopenia, and hypoplastic iliac wings. Conclusions: Few cases have been described, as this is a rare skeletal dysplasia. This paper describes a new familial case of SED-BDS. © The American Journal of Case Reports.
Keywords: Fantasy island syndrome; SED-BDS; Tattoo dysplasia; adolescent; body size; bone disease; bone growth; brachydactyly; brachymetacarpy; brachymetatarsalia; Brazilian; case report; epiphysis; ethnic group; familial disease; foot; genetic disorder; growth retardation; hand; human; hypoplastic iliac wings; limb; long bone; lumbar hyperlordosis; male; ossification; osteopenia; physical examination; scoliosis; short stature; spondyloepiphyseal dysplasia brachydactyl and distinctive speech; vertebra malformation